Potential impact of different LED light spectra on callus induction, regeneration and plantlet growth of two cultivars of Caladium bicolor - Maryam Dehestani-Ardakani; Mohsen Karimi Dorche; Maryam Rahmati (Journal of Horticulture and Postharvest Research, 2025)
Purpose: Caladium bicolor is highly valued as both a landscape and indoor plant, primarily for its decorative appeal stemming from its diverse leaf shapes and vibrant, multicolored foliage. LED (light-emitting diode) lighting serves as a cost-efficient and potent means of promoting plant growth and development. The impact of different LED lights was investigated on callus induction, regeneration, and plantlet growth of two cultivars of Caladium bicolor (‘White’ and ‘Red’). Research Method: Leaf explants were cultured on Murashige and Skoog (MS) medium supplemented with 1.5 mg L-1 IBA and 1 mg L-1 BA and moved to racks equipped with various LED lighting (100% red lights (R), 100% blue lights (B), 50% blue + 50% red lights (B+R), and 100% white fluorescent lamps (W)). Findings: Results showed W light was the best for maximum callus induction, leaf number, and plantlet height in both cultivars. Red + blue LED light spectrum motivated proliferation percentage of callus in both cultivars as compared to other light spectra. Conservation of ‘White’ caladium plantlets in R and B light spectra resulted in no hyperhydric micro shoot formation incidences. When examining various growth characteristics, it was evident that the B+R light spectrum of ‘Red’ caladium showed the best performance, while the B light spectrum in both cultivars had the least favorable outcomes compared to all other light spectra. Research limitations: There was no limitation. Originality/Value: Our findings offer a deeper understanding of how the quality of LED light impacts the in vitro propagation of caladium, potentially enhancing the cultivation of these plantlets through specific spectral exposure.